Sociopreneurship Development Strategy for Local Wisdom-Based Business Actors at the Kampung Bathok Industrial Center in Blitar - Ike Wardani, Shanti; Widayani, Anna (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to examine the development strategy of local wisdom-based sociopreneurship in the home industry center of Kampung Bathok Blitar. This village has potential products made from coconut shells that reflect cultural values and environmental sustainability. The integration of local values such as the use of natural materials by utilizing coconut shell waste, the spirit of mutual cooperation, and the preservation of cultural arts characterize the practice of sociopreneurship in the area. However, challenges such as limited market access, lack of production technology, and low participation of the younger generation hinder business development. Through a qualitative approach, this research identifies development strategies that include product diversification, digital marketing, strategic partnerships and human resource training. These strategies aim to improve business competitiveness, expand market access, and involve the younger generation in preserving cultural values. The results show that a local wisdom-based approach can be a sustainable sociopreneurship model, providing positive economic, social, and environmental impacts.